Factions in British and American Unions – A Comparative Structural Approach - Warner, Malcolm; Edelstein, J. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1973)
In this paper, the authors attempt to discuss the relationship between intra-organizational conflict and factionalism, and how this manifests itself in different ways in British and American unions. They start with a discussion of conflict, then attempt to set out the characteristics of fractions, They next look at factionalism comparatively, and finally attempt an analytical framework which looks at the dimensions of factionalism.